Factors Influencing Labor Market Dynamics in Médéa Province : An Analytical Study Using Econometric modeling for the period 2010-2020 - benaissa, sarra; djaider, hassane (Journal of Excellence for Economics and Management Research, 2025)
this study aims to analyze the factors influencing the dynamics of the labor market in Medea province using an analytical approach supported by econometric modeling. The importance of the topic stems from its close link to the issues of unemployment and the weak creation of job opportunities. The theoretical framework of the article was built by addressing the determinants of the labor market and the economic and demographic factors affecting it, in addition to reviewing theories related to employment and inclusive growth. The study tackled the central problem of identifying the most influential factors affecting the unemployment rate movements in the province during the period (2010-2020) ,through the application of a suitable econometric model and precise scientific analysis of time series data . The study results revealed a strong inverse relationship between economic growth and the unemployment rate, as well as the positive impact of public investment and social spending on stimulating labor market dynamics. Econometric tests confirmed the models validity and the absence of problems such as autocorrelation and heteroskedasticity. The study recommends adopting more flexible local economic policies aimed at supporting labor-intensive sectors, improving the business environment; and encouraging private investment to effectively contribute to reducing unemployment rates in Medea province.